1992
DOI: 10.1002/jnr.490320414
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol esters modulate phospholipid metabolism in a human cholinergic cell line, LA‐N‐2: A possible role for the base exchange enzymes

Abstract: It was shown that in LA-N-2 cells prelabeled with [3H-methyl]choline for 24 hr (Singh et al.: Mol Chem Neuropathol 14:53-66, 1991) the major intracellular and extracellular hydrophilic compound was phosphorylcholine. LA-N-2 cells were labeled with [14C-methyl]choline for 24 hr, harvested, and incubated in Hepes/BSA/saline buffer for varying periods of time. The radioactive compound present in the cytosol and released into Hepes/BSA/saline buffer medium in the presence or absence of TPA was phosphorylcholine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Little information is available on the regulation of PtdSer biosynthesis. It was reported that TPA (12-O-tetradecanoylphorbol 13-acetate) increased serine incorporation into PtdSer in neuroblastoma LA-N-2 cells (Singh et al, 1992) but inhibited PtdSer synthesis in glioma C6 cells (Czarny et al, 1995).…”
Section: Biosynthesis Of Phosphatidylserine-base-exchange Reactionmentioning
confidence: 99%
“…Little information is available on the regulation of PtdSer biosynthesis. It was reported that TPA (12-O-tetradecanoylphorbol 13-acetate) increased serine incorporation into PtdSer in neuroblastoma LA-N-2 cells (Singh et al, 1992) but inhibited PtdSer synthesis in glioma C6 cells (Czarny et al, 1995).…”
Section: Biosynthesis Of Phosphatidylserine-base-exchange Reactionmentioning
confidence: 99%